Like a hotel, but boring: users' experience with short-time community-based residential aftercare - Eirik Roos; Ottar Bjerkeset; Margrét Hrönn Svavarsdóttir; Aslak Steinsbekk (BMC, 2017)
Abstract Background The discharge process from hospital to home for patients with severe mental illness (SMI) is often complex, and most are in need of tailored and coordinated community services at home. One solution is to discharge patients to inpatient short-stay community residential aftercare (CRA). The aim of this study was to explore how patients with SMI experience a stay in CRA established in a City in Central Norway. Methods A descriptive qualitative study with individual interviews and a group interview with 13 persons. The CRA aims to improve the discharge process from hospital to independent supported living by facilitating the establishment of health and social services and preparing the patients. The philosophy is to help patients use community resources by e.g. not offering any organized in-house activities. The main question in the interviews was "How have you experienced the stay at the CRA?" The interviews were analyzed with a thematic approach using systematic text condensation. Results The participants experienced the stay at the CRA "Like a hotel" but also boring, due to the lack of organized in-house activities. The patients generally said they were not informed about the philosophy of the CRA before the stay. The participants had to come up with activities outside the CRA and said they got active help from the staff to do so; some experienced this as positive, whereas others wanted more organized in-house activities like they were used to from mental health hospital stays. Participants described the staff in the CRA to be helpful and forthcoming, but they did not notice the staff being active in organizing the aftercare. Conclusions The stay at the CRA was experienced as different from other services, with more freedom and focus on self-care, and lack of in-house activities. This led to increased self-activity among the patients, but some wanted more in-house activities. To prepare the patients better for the stay at the CRA, more information about the philosophy is needed in the pre-admission process.